Cold fluids improve exercise performance in the heat by slowing the rate of heat gain - Marino, F. E.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2009)
Zuschrift zum Artikel "Cold drink ingestion improves exercise endurance capacity in the heat" (Lee, J. K. W. et al. in Med. Sci. Sports exerc. 2008, 40 (9), S. 1637-1644).